Event marketing: an innovative promotional tool and its impact on consumer memory and brand awareness - Ribeiro, Catarina Peres (2015)
Event Marketing represents a common promotional strategy that involves direct contact between brands and consumers at special events, namely concerts, festivals, sporting events and fairs. Brands have been investing in sponsorship as a means of associating themselves with particular events, essentially with the goal to enhance brand image and brand awareness. Interestingly, the response of consumers to event marketing has not yet been fully understood. This dissertation fills this gap. More specifically, it intends to determine the extent to which sponsoring brands at events favors brand awareness (recall and recognition) and how it relates to brand attitude. Based on three Portuguese music festivals, two studies were conducted to ascertain event sponsorship’s impact on consumer memory, notably Brand Recall and Brand Recognition, and correlation with attitudes towards the brands such as familiarity and liking. The key findings of these studies show that recognition is much higher for those respondents who attended the festivals, presenting a score of 73,9%, in comparison with recall, presenting a much lower score of 37,5%. Further, and surprisingly, it suggests that the ability to recall and recognize sponsoring brands is not associated to consumer attitudes towards the brands. Instead, it relates to the time consumers dedicated to these particular events, that is, the number of music festivals attended.